ANALISIS NPL, LDR, DAN CAR TERHADAP KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DI PROVINSI KALIMANTAN: ANALISIS NPL, LDR, DAN CAR TERHADAP KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DI PROVINSI KALIMANTAN - Safitri, Aista; Perdana, Ariefanda Iqbal; Haryono, Haryono (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2024)
Banks are financial institutions that collect public money through deposits and back it to the community through credit. The function of BPD is to encourage the creation of regional economic growth, hold cash, and manage regional finances, as well as one of the sources of local revenue. This study aims to analyze the effect of NPL, LDR, and CAR on financial performance projected by ROA. The population of this study is a regional development bank in Kalimantan Province, namely, as many as four companies for the period 2013-2022. Three companies were obtained as samples based on the purposive sampling technique. The data analysis technique used is multiple linear regression. The results showed that (1) NPL has a negative and insignificant effect on ROA, (2) LDR has a positive and significant effect on ROA, and (3) CAR has no significant effect on ROA.